Physical Activity, Sport Practice and Cardiovascular Risk Factors in Workers From a Public Hospital: A Trajectory Analysis - Marques Elias, Rui Gonçalves; Ieker, Ana Silvia Degasperi; Reis, Lucas Lopes dos; Stabelini Neto, Antônio; Sasaki, Jeffer Eidi; Lopes, Wendell Arthur; Costa, Carla Eloise; Rinaldi, Wilson (Frontiers in Cardiovascular Medicine, 2021)
Background: Studies have demonstrated the positive effects of physical activity on cardiovascular risk factors. Longitudinal studies using modeled trajectories are necessary to understand patterns of physical activity and association with cardiovascular risk factors. Objective: To analyze the association between sports practice in young people and current physical activity with the trajectory of cardiovascular risk factors in workers at a public hospital. Methods: 417 workers was followed for four years reporting Physical Activity, health status, lifestyle behaviors and socio-demographic characteristics. Group-based trajectory modelling identified the trajectories of PA and associations with time-stable and time-varying covariates. We considered a range of sociodemographic and health and lifestyle factors as potential covariates. Results: The results shows the association between participation in sports activities in youth and current physical activity and trajectories of cardiovascular risk, adjusted for sex and age (p<0,05). Adults who reported having played sports in their youth and are currently active have a lower risk of having a history of obesity and low HDL-c than workers who did not play sports in their youth and are currently sedentary 0.690 (0.565-0.844) obesity, 0.647 (0.500-0.837) low HDL-c.Conclusion: The practice of sports in youth and current physical activity is a protective factor against the trajectory of obesity and low HDL-c, mainly in female workers. Programs to encourage the practice of physical activity should be carried out in order to reduce cardiovascular risk factors and prevent chronic diseases in workers.